2022
DOI: 10.1111/obes.12514
|View full text |Cite
|
Sign up to set email alerts
|

Robust Correlates of Growth Spells: Do Inequality and Redistribution Matter?

Abstract: Theoretical and empirical evidence on inequality and growth provides only partial guidance about the relationship. Much of the problem stems from model uncertaintyabout what covariates to use, the relationships between them, and the transmission mechanisms-which is often not properly accounted for. This paper investigates the relationship between growth, redistribution, and the duration of growth spells in the presence of a rich set of alternative determinants and theories using model averaging for duration mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…They found that a shock to inequality has a negative impact on growth. Kourtellos and Tsangarides (2022) found that lower net inequality is associated with longer growth periods. Redistribution does not appear to be correlated with the length of growth periods.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a shock to inequality has a negative impact on growth. Kourtellos and Tsangarides (2022) found that lower net inequality is associated with longer growth periods. Redistribution does not appear to be correlated with the length of growth periods.…”
Section: Introductionmentioning
confidence: 99%